2005
DOI: 10.1007/s10541-005-0143-y
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic DNA Methylation Is an Epigenetic Control for Genetic Functions of the Cell

Abstract: In eukaryotic cells nuclear DNA is subjected to enzymatic methylation resulting in formation of 5-methylcytosine residues mainly in CG and CNG sequences. In plants and animals, this DNA methylation is species-, tissue-, and organelle-specific. It changes (diminishes) with age and is regulated by hormones. On the other hand, genome methylation can control hormonal signal. There are replicative and post-replicative DNA methylations. They are served by multiple DNA-methyltransferases with different site specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 60 publications
1
49
0
8
Order By: Relevance
“…After their initial insertion, retrotransposons (RTs) undergo transcriptional silencing, which involves CpG methylation in DNA (58) and may also involve repressive modifications of histones. The ''genome defense'' hypothesis suggests that CpG methylation initially arose in evolution for silencing and neutralizing the gene activities of transposable elements and was subsequently recruited for repression of genes (59) but there are other hypotheses on the evolutionary origin of DNA methylation.…”
Section: Modulation Of Biological Effects Of Retroelements By Their Ementioning
confidence: 99%
“…After their initial insertion, retrotransposons (RTs) undergo transcriptional silencing, which involves CpG methylation in DNA (58) and may also involve repressive modifications of histones. The ''genome defense'' hypothesis suggests that CpG methylation initially arose in evolution for silencing and neutralizing the gene activities of transposable elements and was subsequently recruited for repression of genes (59) but there are other hypotheses on the evolutionary origin of DNA methylation.…”
Section: Modulation Of Biological Effects Of Retroelements By Their Ementioning
confidence: 99%
“…It is also characterized by specificity within particular tissues, organelles and species (VANYUSHIN 2005). BOCKLANDT et al (2011) also found that the methylation level in individual genes substantially increased with the age of the organism.…”
Section: Discussionmentioning
confidence: 97%
“…In vertebrates, widespread epigenetic modification of genomic DNA has been detected most commonly as methylation at the 5′ position of cytosine (5-methylcytosine) within symmetric 5′-CpG-3′ (CpG) dinucleotide sequences. In addition, 5-methylcytosines have been found within asymmetric, non-CpG sequences in mammals, including humans, as well as in plants (Clark et al, 1995;Wada et al, 2003;Inoue and Oishi, 2005;Vanyushin, 2005). In the genomes of bacteria, protists, fungi, and plants, N 6 -methyladenine is found at the internal adenine within 5′-TGATCA-3′ sequences (Vanyushin, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 5-methylcytosines have been found within asymmetric, non-CpG sequences in mammals, including humans, as well as in plants (Clark et al, 1995;Wada et al, 2003;Inoue and Oishi, 2005;Vanyushin, 2005). In the genomes of bacteria, protists, fungi, and plants, N 6 -methyladenine is found at the internal adenine within 5′-TGATCA-3′ sequences (Vanyushin, 2005). Although detection of N 6 -methyladenine in animal cells has not been reported, open reading frame DNA sequences homologous to bacterial adenine DNAmethyltransferases have been found in the genomes of insects, nematodes, and vertebrates, including humans, raising the possibility of the presence of adenine methylation in higher eukaryotes (Baniushin, 2005;Vanyushin, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation